2003
DOI: 10.1002/jemt.10395
|View full text |Cite
|
Sign up to set email alerts
|

Siliceous spicules and skeleton frameworks in sponges: Origin, diversity, ultrastructural patterns, and biological functions

Abstract: Silica deposition is a fundamental process in sponges. Most sponges in the Classes Demospongiae and Hexactinellida secrete siliceous elements, which can subsequently fuse, interlock with each other, or form three-dimensional structures connected by spongin. The resulting skeletal frameworks allow sponges to grow upwards and facilitate water exchange with minimal metabolic cost. Several studies on sponge skeletogenesis have been published. We are beginning to understand the mechanisms of spicule secretion and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
161
0
6

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 216 publications
(180 citation statements)
references
References 84 publications
5
161
0
6
Order By: Relevance
“…The major reason for studying the structure of the spicules here has been to understand the growth pattern of the spicules in an axial and radial direction. All (or almost all) spicules of M. chuni are open at their tips (Schulze 1904;Uriz 2006;Uriz et al 2003); their axial canals occasionally expose the axial filaments. This finding has contributed to the understanding of the axial growth of the spicules (see below).…”
Section: -------------------------------------------mentioning
confidence: 99%
See 1 more Smart Citation
“…The major reason for studying the structure of the spicules here has been to understand the growth pattern of the spicules in an axial and radial direction. All (or almost all) spicules of M. chuni are open at their tips (Schulze 1904;Uriz 2006;Uriz et al 2003); their axial canals occasionally expose the axial filaments. This finding has contributed to the understanding of the axial growth of the spicules (see below).…”
Section: -------------------------------------------mentioning
confidence: 99%
“…Electron-microscopic studies have revealed that the tips of the spicules from this hexactinellid can be distinguished from those found in Demospongiae (Uriz et al 2003), since all of them are open (Schulze 1904). The images show that the characteristic quadratic opening, viz., the axial canal, occasionally possesses an axial filament that reaches the upper edges of the top orifice.…”
Section: -------------------------------------------mentioning
confidence: 99%
“…Поткласа Традиционално се систематика разреда Porifera заснивала на спикулама, чија се морфологија и еволуција исцрпно истраживала (Dendy, 1921;Jones, 1997;Uriz et al, 2003), али информације које оне пружају су ограничене да би се могла ријешити проблематика класификације спужви. Друге морфолошке особине попут облика, грађе и боје, зависе од услова средине, па се не могу узети као таксономски карактер.…”
Section: уводunclassified
“…Through complex enzymatic and metabolic processes (Wang et al, 2011a(Wang et al, ,b, 2012a, siliceous species of Hexactinellida, Demospongiae and Homoscleromorpha take up Si (predominantly present as silicic acid, H 4 SiO 4 and conventionally referred to as dissolved silica; dSi) from their surrounding water to secrete individual structures known as spicules which provide skeletal support to the organic components of the sponge (Uriz et al, 2003). In some species of hexactinellids and demosponges, skeletal structures are massive and hypersilicified, with stony consistency and can form agglomerates and build reef-like formations (Conway et al, 2001;Uriz et al, 2003;Leys et al, 2004;Maldonado et al, 2015a,b) or "sponge grounds" (Klitgaard and Tendal, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…In some species of hexactinellids and demosponges, skeletal structures are massive and hypersilicified, with stony consistency and can form agglomerates and build reef-like formations (Conway et al, 2001;Uriz et al, 2003;Leys et al, 2004;Maldonado et al, 2015a,b) or "sponge grounds" (Klitgaard and Tendal, 2004). Sponges of these groups may be important players in the global silicon cycle due to their widespread occurrence and high preservation potential (Maldonado et al, 2005(Maldonado et al, , 2010.…”
Section: Introductionmentioning
confidence: 99%